2019
DOI: 10.3892/ijo.2019.4710
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of protein disulfide‑isomerase A3 expression inhibits cell proliferation and induces apoptosis through STAT3 signaling in hepatocellular carcinoma

Abstract: Protein disulfide-isomerase A3 (PDIA3) is a chaperone protein that modulates folding of newly synthesized glycoproteins and responds to endoplasmic reticulum (ER) stress. Previous studies reported that increased expression of PDIA3 in hepatocellular carcinoma (HCC) is a marker for poor prognosis. However, the mechanism remains poorly understood. The aim of the present study, therefore, was to understand the role of PDIA3 in HCC development. First, immunohistochemical staining of tissues from 53 HCC cases revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 43 publications
(53 reference statements)
2
32
0
Order By: Relevance
“…We confirmed the role of PDIA1 in regulating the cell cycle and apoptosis, which was translated into a noticeable anti-cancer effect in the colony formation assay but not a substantial anti-proliferation effect in the classical assays. Altogether, our results showed that, apart from the tumorigenic role of intracellular PDI in the ER [ 33 ], PDIA1 played a vital role in regulating the adhesion of cancer cells and their transendothelial migration. The latter effects could be attributed to the extracellular PDIA1 function of regulating integrin-mediated adhesion and subsequent transendothelial migration of breast cancer cells, but not to the PDIA1-dependent regulation of ICAM-1 expression or changes in cellular bioenergetics in breast cancer or endothelial cells.…”
Section: Discussionmentioning
confidence: 92%
“…We confirmed the role of PDIA1 in regulating the cell cycle and apoptosis, which was translated into a noticeable anti-cancer effect in the colony formation assay but not a substantial anti-proliferation effect in the classical assays. Altogether, our results showed that, apart from the tumorigenic role of intracellular PDI in the ER [ 33 ], PDIA1 played a vital role in regulating the adhesion of cancer cells and their transendothelial migration. The latter effects could be attributed to the extracellular PDIA1 function of regulating integrin-mediated adhesion and subsequent transendothelial migration of breast cancer cells, but not to the PDIA1-dependent regulation of ICAM-1 expression or changes in cellular bioenergetics in breast cancer or endothelial cells.…”
Section: Discussionmentioning
confidence: 92%
“…In the present study, the mRNA and protein expression levels of ISG15 in HCC tissues were found to be significantly increased in HCC tissues. Furthermore, according to the previous studies (2022), the clinicopathological significance of ISG15 levels in patients with HCC was further investigated in the current study. It was observed that ISG15 levels in HCC tissues were significantly correlated with tumor size, TNM stage and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Patient characteristics are listed in Table I. The clinicopathological significance of ISG15 levels in patients with HCC was studied according to methods described in the previous studies (2022). Following surgical resection, the tissue samples were immediately snap frozen in liquid nitrogen and stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Liver cancer with high PDIA3 expression follows an unfavorable course and is characterized by high proliferation activity and a low frequency of cell death. The expression of PDIA3 and its association with prognosis has been reported for other carcinomas (21,22,(38)(39)(40)(41). Furthermore, knock-down of PDIA3 may enhance the effect of radiation therapy in laryngeal cancer (38) and breast cancer (42).…”
Section: Discussionmentioning
confidence: 82%
“…PDIA3 is involved in the assembly and stability of signaling molecules such as mTOR and STAT3 (19,22). It has been shown that PDIA3 forms a complex with mTORC1 and stabilizes the signaling pathway (23).…”
Section: Introductionmentioning
confidence: 99%